2022
DOI: 10.3390/ani12182348
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chemical Composition and In Vitro Methane Production of High Andean Grasses

Abstract: The present study aims to establish the relationship between chemical composition and in vitro methane (CH4) production of high Andean grasses. For this purpose, eight species were collected in dry and rainy seasons: Alchemilla pinnata, Distichia muscoides, Carex ecuadorica, Hipochoeris taraxacoides, Mulhenbergia fastigiata, Mulhenbergia peruviana, Stipa brachiphylla and Stipa mucronata. They were chemically analyzed and incubated under an in vitro system. Species such as A. pinnata and H. taraxacoides were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…All these resources had a high content of NDF and ADF. The negative correlation between NDF level and gas production was consistent with other studies [ 31 , 32 ], in which a reduction in gas production with increasing of NDF content of the substrates was reported. In general, the present results were lower than those found in the literature [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…All these resources had a high content of NDF and ADF. The negative correlation between NDF level and gas production was consistent with other studies [ 31 , 32 ], in which a reduction in gas production with increasing of NDF content of the substrates was reported. In general, the present results were lower than those found in the literature [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…[61]. The acetic, propionic and butyric acids were between the range observed in tropical grasses [44,61]; similarly, the observed methane and ammonia concentrations [50,62]. These results demonstrate the productive potential of the evaluated pastures, which constitutes them as a valuable forage resource to be considered as a food source for grazing cattle, during the flooding times occurring within the floodable savannah ecosystem in the Colombian Orinoquia.…”
Section: In Vitro Fermentation Characteristicssupporting
confidence: 57%
“…One of the aims of the present study was to evaluate the effect of the feeding level on dietary N utilization. Depending on the plant species, the CP contents of native grasses in the Peruvian Altiplano can decrease up to (or even below) 40 g/kg DM during the dry season [16]. In the study by Huareccallo Maquera [42], the total N intake was calculated to be 11.7 and 13.0 g/d for the 40 and 50 g of DM/kg BW 0.75 feeding levels, respectively (CP of the diet: 92 g/kg DM).…”
Section: Carbon and Nitrogen Balancesmentioning
confidence: 99%
“…Despite the reduced nutritional quality of the Peruvian Altiplano rangelands during the dry season [15][16][17], earlier studies have shown that adult alpacas counterbalance this situation by increasing their intake of Festuca dolichophylla/Muhlenbergia fastigiata swards up to 12% when compared to their observed intake during the rainy season [18]. This is explained by the observed increase in the gastric capacity of these animals in response to the reduced forage quality [11].…”
Section: Introductionmentioning
confidence: 99%